1992
DOI: 10.1046/j.1537-2995.1992.32993110760.x
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemotaxis and chemotactic cytokine release after exposure to hydroxyethyl starch

Abstract: Hydroxyethyl starch (HES) is commonly used in leukapheresis and infused as an alternative to blood components for the treatment of hypotension due to hemorrhage and trauma. Its prolonged intravascular persistence and retention In tissue raise concerns about possible effects on humoral and cell-mediated immunity and white cell (WBC) locomotion, particularly in volunteer WBC donors or in severel burned evaluated the effect of HES on human mono e migration and chemotaxis and the bioassay was developed to quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
11
1
1
Order By: Relevance
“…In an in vitro study Sillet et al [104] demonstrated that T cell activation and mitogenic responses are not inhibited in the presence of dextran, gelatin or HES, implying no immunodepression by colloidal resuscitation fluids. The timeand dose-dependent generation of a chemotactic cytokine was not affected by the presence of HES [105]. HES by itself did not induce cytokine generation, nor were chemotaxis and spontaneous migration of human monocytes affected [105].…”
Section: Immune Systemmentioning
confidence: 85%
See 1 more Smart Citation
“…In an in vitro study Sillet et al [104] demonstrated that T cell activation and mitogenic responses are not inhibited in the presence of dextran, gelatin or HES, implying no immunodepression by colloidal resuscitation fluids. The timeand dose-dependent generation of a chemotactic cytokine was not affected by the presence of HES [105]. HES by itself did not induce cytokine generation, nor were chemotaxis and spontaneous migration of human monocytes affected [105].…”
Section: Immune Systemmentioning
confidence: 85%
“…The timeand dose-dependent generation of a chemotactic cytokine was not affected by the presence of HES [105]. HES by itself did not induce cytokine generation, nor were chemotaxis and spontaneous migration of human monocytes affected [105].…”
Section: Immune Systemmentioning
confidence: 85%
“…Nach der Gabe von kolloidalen Volumenersatzmitteln werden diese in verschiedenen Organsystemen [5,10,20] …”
Section: Diskussionunclassified
“…However, small amounts of HES are taken up by monocytes/macrophages, particularly in the liver and spleen [2,3], raising the possibility of detrimental effects. Studies involving healthy volunteers have confirmed the lack of detrimental effects on chemotaxis and phagocytosis [10][11][12]. Studies involving healthy volunteers have confirmed the lack of detrimental effects on chemotaxis and phagocytosis [10][11][12].…”
Section: Introductionmentioning
confidence: 97%